Airports: places or non-places - who cares? - Losekoot, E (Council for Australasian Tourism and Hospitality Education (CAUTHE), 2015)
There is considerable literature on the concept of placelessness (Relph, 1976) and ‘nonplace’ (Augé, 1995). Much of this comes from the geography literature, but the developing area of ‘mobilities’ (Sheller & Urry, 2006; Urry, 2002) opens this discussion to include those working in tourism and hospitality. Many examples (e.g. Merriman, 2004) use transport hubs such as airports, train stations and motorway service stations as research sites, yet some locations appear to have been very successful in creating an identity where there was little before (Lohmann, Albers, Koch & Pavlovich, 2009). This study gathered qualitative data from 120 airport customers of Auckland International Airport in New Zealand. The paper will consider whether those people expressed the feeling that airports are liminal spaces (Turner, 1969) which become ‘non-places’ as a result of being ‘spaces in transition’. Using Auckland Airport as a case study it considers what airport customers feel is important in terms of giving a location an identity, and what this particular airport is doing to meet those needs.
Keywords: Airport; Customer experience; Non-place; Placelessness; Transport